Down‐regulation of crambe fatty acid desaturase and elongase in Arabidopsis and crambe resulted in significantly increased oleic acid content in seed oil. Issue 1 (21st May 2015) - Li, Xueyuan; Mei, Desheng; Liu, Qing; Fan, Jing; Singh, Surinder; Green, Allan; Zhou, Xue‐Rong; Zhu, Li‐Hua
Summary: High oleic oil is an important industrial feedstock that has been one of the main targets for oil improvement in a number of oil crops. Crambe ( Crambe abyssinica ) is a dedicated oilseed crop, suitable for industrial oil production. In this study, we down‐regulated the crambe fatty acid desaturase ( FAD ) and fatty acid elongase ( FAE ) genes for creating high oleic seed oil. We first cloned the crambe CaFAD2, CaFAD3 and CaFAE1 genes. Multiple copies of each of these genes were isolated, and the highly homologous sequences were used to make RNAi constructs. These constructs were first tested in Arabidopsis, which led to the elevated oleic or linoleic levels depending on the genes targeted, indicating that the RNAi constructs were effective in regulating the expression of the target genes in nonidentical but closely related species. Furthermore, down‐regulation of CaFAD2 and CaFAE1 in crambe with the FAD2 – FAE1 RNAi vector resulted in even more significant increase in oleic acid level in the seed oil with up to 80% compared to 13% for wild type. The high oleic trait has been stable in subsequent five generations and the GM line grew normally in greenhouse. This work has demonstrated the great potential of producing high oleic oil in crambe, thus contributing to its development into an oil crop platform for industrial oil production.